Community development programmes in Malaysia - Abu Samah, Asnarulkhadi; Aref, Fariborz (Marsland Press, 2009)
This study looks at the philosophy, policy development and practices of community development as well as rural development programmes in Malaysia. The history of community development and its policy is important for provide community development processes to date. Since independence, the Malaysian government has introduced various types of community development programmes through its development policies, with the main of improving the economic, social and cultural conditions of the people. Understanding of these programmes can help to community leaders and stakeholders to achieve future programmes for realize community goals.